2012
DOI: 10.1523/jneurosci.4057-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Three Types of Neurochemical Projection from the Bed Nucleus of the Stria Terminalis to the Ventral Tegmental Area in Adult Mice

Abstract: /VGluT3ϩ terminals, which should include those from GAD67 ϩ /VGluT3 ϩ BST neurons, formed symmetrical synapses. When single axons from VGluT3 ϩ BST neurons were examined, almost all terminals were labeled for VIAAT, whereas VGluT3 was often absent from terminals with high VIAAT loads. VGluT2 ϩ terminals in the VTA exclusively formed asymmetrical synapses, which expressed AMPA receptors on postsynaptic membrane. Therefore, the major mode of the BST-VTA projection is GABAergic, and its activation is predicted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
160
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 59 publications
14
160
0
1
Order By: Relevance
“…Indeed, BNST-A contains a small group of glutamatergic cells interspersed among a dominant population of GABAergic neurons (Day et al 1999;Esclapez et al 1993;Hur and Zaborszky 2005;Kudo et al 2012;Poulin et al 2009;Sun and Cassell 1993). Moreover, BNST-A neurons express numerous peptides than can coexist in various combinations (Woodhams et al 1983).…”
Section: Morphological Correlates Of Electroresponsive Propertiesmentioning
confidence: 99%
“…Indeed, BNST-A contains a small group of glutamatergic cells interspersed among a dominant population of GABAergic neurons (Day et al 1999;Esclapez et al 1993;Hur and Zaborszky 2005;Kudo et al 2012;Poulin et al 2009;Sun and Cassell 1993). Moreover, BNST-A neurons express numerous peptides than can coexist in various combinations (Woodhams et al 1983).…”
Section: Morphological Correlates Of Electroresponsive Propertiesmentioning
confidence: 99%
“…A majority of BNST cells are GABAergic/peptidergic and a minority (Day et al 1999;Poulin et al 2009;Kudo et al 2012). Given the pattern of results obtained in retrograde tracing studies (Day et al 1999;Herman et al 2004;Kudo et al 2012), it is likely that a large proportion of the GABAergic cells and at least some of the glutamatergic neurons are projection cells.…”
mentioning
confidence: 99%
“…A majority of BNST cells are GABAergic/peptidergic and a minority (Day et al 1999;Poulin et al 2009;Kudo et al 2012). Given the pattern of results obtained in retrograde tracing studies (Day et al 1999;Herman et al 2004;Kudo et al 2012), it is likely that a large proportion of the GABAergic cells and at least some of the glutamatergic neurons are projection cells. Similarly, although electrophysiological studies have distinguished three main cell types in BNST-AL (Hammack et al 2007;Hazra et al 2011;Rodríguez-Sierra et al 2013), it remains unclear whether all or a subset of each class correspond to projection cells or interneurons.…”
mentioning
confidence: 99%
“…Since, pharmacological inhibition of the BNST (but not the amygdala) by the GABA-A receptor agonist muscimol was shown to disrupt fear responses to TMT [32] [54], and since, increased anxiety levels were reported after inactivation of GABA synthesis within the BNST [59], it can be assumed that GABAergic mechanisms in the BNST are involved in TMT-induced innate fear responses. It was already shown that GABAergic BNST neurons can inhibit the HPA axis via direct projections to the PVN [58], and by the way of GABA-GABA disinhibitory connections [60], the amygdala is in a position to cause a stress-induced activation of the HPA axis. Since, stressful events, like the exposure to a predator odor, are able to activate GABAergic neurons within the BNST [61] a delivering of the BNST from the inhibitory GABAergic influence of the amygdala can be supposed.…”
Section: Discussionmentioning
confidence: 99%